Monitoring and management insect pest on cocoa (Theobroma cacao) at Ladang UiTM Jasin / Syahirah Jasmin Zainon - Zainon, Syahirah Jasmin (Faculty of Plantation and Agrotechnology, 2018)
Cocoa known as Theobroma cacao become famous as food ingredient in confection industry through worldwide. Cocoa has become major source for 1.4 million people in the country. Nonetheless, infestation of insect had affect the quality of cocoa beans which has resulting affected the grade and cause low price of cocoa. Improper management in cocoa field leads severe damage on cocoa at Ladang UiTM Jasin. Cocoa Pod Borer (CPB) caused severe damage which capable to cause complete crop loss. The objective of this study were to identify the insect pest and to determine effective pest control methods for cocoa at Ladang UiTM Jasin. This study intend purposely to collect data of the insect pest. The data collected from 29th January 2018 until 4th March 2018. yellow sticky trap was used in this study to identify pest population on cocoa. Several pest control methods such as cultural control, chemical control, combination of cultural and chemical control were conducted properly. The results showed six order of insect were recorded Order Hymenoptera recorded was the highest population in Ladang UiTM Jasin. Combination of cultural and chemical control resulted the best control methods to control insect pest at Ladang UiTM Jasin.